UNITY IN IDENTITY OR UNITY IN ENTITY? SHARING OR POSSESSING CHRIST? - BAIRACTARIS, Augustinos (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
Without any question, ecclesiology along Christology remain the crucial issues for theologians in the modern Ecumenical dialogue. And while we take as granted that we, as Christians coming from different Churches, have reached a common place regarding the doctrines of Christology, at the same time we experience and we live within our various confessional bodies a different Christ. We are the receivers of the baptismal gift (unum baptisma) and of the calling to be workers of unity, but still, we are living in a “not yet” unity situation. We all witness the paradoxical phenomenon of accepting that baptism bring us in communion with God, but not with one another, exceptionally not with those who come from different Christian denomination. We are “already” in God’s grace, but “not yet” in that same gracious acceptance of one another. We tend to want to correct each other before we encourage one another; to judge before we accept. Statements of faith tend to carry more value than acts of faith. This paper aims to answer the question of the ecclesial unity.